Quantum corrections to the Vlasov description of collective modes - Salem, L. D.; Wio, Horacio Sergio (Comisión Nacional de Energía Atómica; Argentina)
Fil: Salem, L. D. Comisión Nacional de Energía Atómica; Argentina